Transformation of marketing strategies in the retail sector through social media: An Islamic values perspective - Ita Ayu Anggina Telaumbanua; Muhammad Syukri Albani Nasution; Atika Atika (LPMP Imperium, 2025)
Digital transformation is pushing retail businesses to adapt their marketing strategies through social media. This study analyzes the integration of social media by SMB MMTC and identifies the opportunities and challenges faced. Using a qualitative case study approach, data was collected through interviews, observations, and documentation at the supermarket located in Medan City. The results show that Instagram, TikTok, and Facebook play a strategic role in expanding market reach, increasing engagement, and strengthening local branding. Challenges include limited human resources, algorithm changes, restricted promotional budgets, and a lack of data-driven evaluation. From an Islamic economic perspective, business practices align with Sharia principles, including transparency, honesty, and freedom from usury and uncertainty. This study concludes that social media functions as both a promotional tool and an interactive platform, with the success of transformation determined by internal readiness, content innovation, and support from a sustainable digital ecosystem. Public Interest Statement: This research is important for the public because it provides insights into how local retail businesses, such as SMB MMTC, can effectively utilize social media to expand their market, increase interaction with consumers, and implement marketing strategies that are in line with Islamic economic principles in the era of digital transformation.